Evaluation of cytotoxicity and genotoxicity effects of refractory pollutants of untreated and biomethanated distillery effluent using Allium cepa - Kumar, Vineet (2022)
Environmental pollution caused by the discharge of raw and partly treated distillery effluent has become a serious and threatening problem due to its high pollution load. The aim of the present study was to assess the physicochemical load in alcohol distillery effluent before and after biomethanation treatment and the cyto- and genotoxicity effects of refractory pollutants emanated in raw/untreated and biomethanated distillery effluent on the ultrastructural and biochemical responses of Allium cepa root tip cells. Physicochemical analysis revealed high biochemical oxygen demand (BOD: 47840-36651 mg L−1), chemical oxygen demand (COD: 93452-84500 mg L−1) and total dissolved solids (TDS: 64251–74652 mg L−1) in raw and biomethanated effluent along with metal(loid)s (Fe: 456.152–346.26; Zn: 1.654–1.465; Cu: 0.648–0.562; Ni: 1.012–0.951, and Pb: 0.264 mg L−1) which were beyond the safe discharge values prescribed by the environmental regulatory agencies. The UV–Visible and Fourier transform infrared spectrophotometry analyses confirmed the high levels of organic, inorganic, and mixed contaminants discharged in raw and biomethanated distillery effluents. Furthermore, GC–MS analysis characterised chemical contaminants, such as hexadecanoic acid, butanedioic acid, bis(trimethylsilyl) ester; hexadecane, 2,6,11,15-tetramethyl, stigmasterol, and β-sitosterol trimethylsilyl ether that have been reported as androgenic-mutagenic, and endocrine disrupting chemicals by the United States Environmental Protection Agency (U.S. EPA). The cytotoxicity measured by A. cepa showed dose depended inhibition root growth inhibition and simultaneous reduction in mitotic index in tested effluents. The chromosomal aberrations studies resulted in laggard chromosomes, sticky chromosomes, vagrant chromosomes, chromosome loss, c-mitosis, chromosome bridge, abnormal metaphase, and disturbed anaphase as found in a dose-dependent manner. Furthermore, dose-dependent enhancement in the levels of malondialdehyde, hydrogen peroxide, and antioxidative enzymes, such as superoxide dismutase, ascorbate peroxidase, and catalase were found to be higher in raw effluents treated root cells compared to biomethanated distillery effluent. Analysis of ultrastructural changes in root tip cells by TEM analysis revealed dramatic changes in the morphology of cell organelles and accumulation of metallic elements in and on the surface tissues. The results concluded that the discharged distillery effluents retained certain toxic pollutants which imposed cytotoxic and genotoxic hazards to A. cepa. Thus, for the sake of environmental protection, the raw as well as the disposed biomethanated effluent must be efficiently treated before its dumping into the terrestrial ecosystem.